2013
DOI: 10.4155/fmc.13.141
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Isoform Selective Hdac Inhibitors for the Treatment of Schizophrenia

Abstract: Increasing evidence supports a role for epigenetic involvement in some of the neurobiological alterations observed in neurodegenerative and psychiatric disorders including schizophrenia. In particular, there is mounting evidence implicating dysfunction in acetylation status, a chromatin modification mediated in part by HDACs, as a possible contributing factor to certain facets of this debilitating disease. Additional data support the notion that small molecule inhibition of HDACs may provide therapeutic altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 87 publications
2
27
1
1
Order By: Relevance
“…We can propose that the AVP deficient Brattleboro rat strain is a valuable model (i) to study the development of SCZ-like behavior, to establish new test battery for SCZ, (ii) follow the changes in epigenetic state of affected genes, and (iii) test newly discovered antipsychotics. This is hotspot as influencing HDACs may provide therapeutic alternatives for treating many of the symptoms associated with SCZ, particularly cognitive deficits [107]. Our studies confirmed that no single gene, more probably fine changes in an array of molecules are responsible for the majority of SCZ cases.…”
Section: Resultssupporting
confidence: 73%
“…We can propose that the AVP deficient Brattleboro rat strain is a valuable model (i) to study the development of SCZ-like behavior, to establish new test battery for SCZ, (ii) follow the changes in epigenetic state of affected genes, and (iii) test newly discovered antipsychotics. This is hotspot as influencing HDACs may provide therapeutic alternatives for treating many of the symptoms associated with SCZ, particularly cognitive deficits [107]. Our studies confirmed that no single gene, more probably fine changes in an array of molecules are responsible for the majority of SCZ cases.…”
Section: Resultssupporting
confidence: 73%
“…Epigenetic evidences also highlight the potential role of DNMT and HDAC inhibitors in the treatment of schizophrenia [103], as summarized in Table 4 [89,99,[104][105][106][107][108][109]. So far both in vitro and animal studies showed that DNMT and HDAC inhibitors reduce DNA methylation of RELN and Table 3.…”
Section: Epigenetics and Pharmacology: Novel Effects Of Old Drugs Andmentioning
confidence: 97%
“…It can thus be hypothesized that antipsychotic drugs, blocking D2-like signaling, induce H3 phosphoacetylation, a dual H3 modification associated with transcriptional activation and epigenetic regulation of gene expression [94]. Distinct antipsychotic classes and subtypes can be differentiated based on their ability to stimulate epigenetic modifications, as summarized in Table 2 [86,90,[94][95][96][97][98][99][100][101][102][103]. Not surprisingly clozapine, the gold standard of treatment-resistant schizophrenia, shows a peculiar profile, compared to other antipsychotics, both typical and atypical.…”
Section: Epigenetics and Pharmacology: Novel Effects Of Old Drugs Andmentioning
confidence: 99%
“…Its promising preliminary data, notably in biochemical and in vitro assays as well as in the NIH cell line, render it an effective potential chemical probe for angiogenisis. 35,36 Current studies are aimed at exploring further SAR in these hybrids with regard to HDAC isoform 37,38 and kinase selectivity 39 as well as improving their physiochemical properties, 40 and will be reported in due course.…”
Section: Discussionmentioning
confidence: 99%